2022
DOI: 10.1108/nfs-12-2021-0391
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of vitamin D2 in edible mushroom using ultraviolet irradiation and assessing its storage and cooking stability

Abstract: Purpose The purpose of this study was to optimize the parameters for enhancing the vitamin D2 formation in three edible mushroom varieties, namely, shiitake mushroom (Lentinula edodes), white button mushroom (Agaricus bisporus) and oyster mushroom (Pleurotus ostreatus) using ultraviolet (UV) irradiation. Design/methodology/approach Freshly harvested mushrooms were irradiated with UV-B and UV-C lamps. Further, mushrooms were treated with UV-B at a distance ranging between 10 and 50 cm from the UV light source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
1
9
2
Order By: Relevance
“…Further, the UVB exposure process for the production of button mushrooms has been approved in European Union under novel food regulation, i.e., regulation (EU) 2015/2283 [ 58 ]. In addition, other studies have reported that the UV exposure has a negative effect on the color of edible mushrooms; however, in our recent study [ 20 ], we observed that there was no significant effect on the color profile of edible mushrooms exposed to UVB for 120 min.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Further, the UVB exposure process for the production of button mushrooms has been approved in European Union under novel food regulation, i.e., regulation (EU) 2015/2283 [ 58 ]. In addition, other studies have reported that the UV exposure has a negative effect on the color of edible mushrooms; however, in our recent study [ 20 ], we observed that there was no significant effect on the color profile of edible mushrooms exposed to UVB for 120 min.…”
Section: Discussioncontrasting
confidence: 87%
“…The optimum conditions for vitamin D 2 enrichment of edible mushrooms derived from our previous study were applied [ 20 ]. Four main factors (moisture content, type of wavelength, distance between UV source and mushroom trays and duration of UV exposure) that can affect vitamin D 2 synthesis were selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known about the long-term retention of D vitamers in dried mushrooms, although there are some studies on both the short-term retention of vitamin D 2 in fresh mushrooms and the long-term retention in frozen, powdered or dried mushrooms. The retention of vitamin D 2 in UV-irradiated fresh mushrooms when refrigerated over periods of up to 14 days have showed varying results, with losses up to 50% [ 24 , 25 , 26 , 27 ]. Wild mushrooms retained virtually all their vitamin D 2 after being frozen for 9 months [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newly generated vitamin D3 enters circulating system from skin by affixing to a protein (vitamin D binding protein). Vitamin D must go through two hydroxylation in order to activate, creating "1,25 [OH]2 D (Malik, Jan, Haq, Kaur, & Panda, 2022). Atherosclerosis patients increased the level of deficiency of calciferol.…”
mentioning
confidence: 99%